In situ nanoarchitectonics of magnesium hydroxide particles for property regulation of carboxymethyl cellulose/poly(vinyl alcohol) aerogels. Issue 56 (1st November 2021) - Qiang, Xiaohu; Guo, Xin; Su, Hongxi; Zhao, Hong; Ouyang, Chengwei; Huang, Dajian
Abstract : Flame retardant efficiency of magnesium hydroxide in cellulose aerogels improved by in situ formation. Abstract : Carboxymethyl cellulose (CMC)-based aerogels with low density, low thermal conductivity, and biodegradability are promising candidates for environmentally friendly heat-insulating materials. However, the application of CMC-based aerogels as insulation materials in building exterior walls is limited by the high water sensitivity, poor mechanical properties and high flammability of these aerogels. In this work, a simple hydration method was used to generate magnesium hydroxide (MH) directly from CMC/polyvinyl alcohol (PVA) mixed sol with active MgO obtained by calcined magnesite as the raw material. A series of composite aerogels with different MH contents were prepared through the freeze-drying method. Scanning electron microscopy showed that nanoflower-like MH was successfully synthesised in situ in the 3D porous polymer aerogel matrix. Compared with the mechanical properties and water resistance of the original CMC/PVA composite aerogels, those of the composite aerogels were significantly improved. In addition, the flame retardancy of the CMC/PVA composite aerogels was greatly enhanced by the introduction of MH into the polymer matrix, and the limiting oxygen index reached 35.5% when the MH loading was 60%.